Answer
Find out the value of g(3) by using the function g(x) = x² + 2 given in the question .
To proof
The function given in the question is
g(x) = x² + 2
Take x = 3
put x = 3 in the g(x) = x² + 2
than it becomes
g(3) = 3² + 2
solving the above
we get
g(3) = 9 + 2
g(3) = 11
Thus g(3) = 11 and option (c) is correct .
Hence proved
That would be around $200. Because you would take 40 devide by .2 and get 200.
Answer:
f(7) = 22 or x =2
Step-by-step explanation:
- f(x) = 3x + 1
- f(7) = 3(7) + 1
- f(7) = 21 + 1
- f(7) = 22
<u>Or if the equation meant it like this:</u>
- f(x) = 3x + 1
- 7 = 3x + 1
- 6 = 3x
- 2 = x
Answer:2/15 hope this helps
Step-by-step explanation:
Answer:
Step-by-step explanation:
The sum of angle measures is ...
(7x +13)° +(83 -2x)° = 141°
5x +96 = 141 . . . . . collect terms, divide by °
5x = 45 . . . . . . . . . subtract 96
x = 9 . . . . . . . . . . . divide by 5
7x +13 = 7·9 +13 = 76 . . . . . find m∠J
m∠J = 76°
m∠K = 141° -76°
m∠K = 65°